Implementasi Prinsip Akad dalam Penggunaan E-Money Mandiri: Analisis Hukum Muamalah terhadap Potensi Gharar, Riba, dan Maisir (Pusat Riset dan Inovasi Nasional, 2026)
The rapid advancement of digital technology has significantly transformed the economic landscape, particularly in payment systems that are shifting from conventional cash transactions to the use of Electronic Money (E-Money). E-Money has become increasingly popular due to the convenience it offers, allowing users to conduct transactions anytime and anywhere without the need to carry physical cash. As this payment innovation continues to expand, it is essential to examine whether its mechanisms comply with Islamic principles, given that the use of E-Money is closely related to the values of muamalah in Islam. This study aims to identify the underlying contractual structure (akad) governing Mandiri E-Money transactions and to assess its conformity with sharia principles. It further analyzes the potential presence of gharar, riba, or maisir within the top-up and transaction processes, as well as the sharia mitigation mechanisms that may be applied. The research employs a normative approach based on classical and contemporary Islamic legal theory, supported by observational analysis of Mandiri E-Money practices. Data were analyzed qualitatively using a descriptive method and maqashid al-shariah reasoning. The findings indicate that the use of Mandiri E-Money does not involve elements of riba, gharar, or maisir, and therefore does not deviate from sharia principles. These potential risks were examined through fiqh legal maxims and DSN-MUI fatwas to ensure comprehensive sharia compliance.